Viruses and virus-like diseases affecting sweet potato subsistence farming in southern Tanzania - Ndunguru, J.; Kapinga, R. (2007)
A survey for sweet potato viruses was conducted in 32 farmer’s fields in Mbinga (20 fields) and Songea (12 fields) districts of the Ruvuma region in Southern Tanzania. Plants showing virus-like symptoms were observed in 25 (78%) out of 32 fields examined. Sweet potato virus disease (SPVD) incidence was low in Mbinga district (16.7%) on average and ranged from 3 to 50% while in Songea district incidence averaged 33% and ranged from 3 to 100%. SPVD incidence difference between the two districts was not statistically significant (P > 0.05) except among sweet potato cultivars (P< 0.05). Sweet potato virus disease severity significantly (P < 0.001) varied between the district with Mbinga having the lowest (2.38 ± 0.2) and Songea the highest (3.26 ± 0.12) mean severity score. SPVD severity score also significantly varied among sweet potato cultivars (P < 0.001) with cultivar ‘‘Jeshi’’ displaying the most severe symptoms (4.2 ± 0.37 severity score) and ‘Wino’ and ‘Madaresalama expressing the mildest symptoms (2.0 ± 0.00). Twenty foliar samples from infected plants were tested serologically for Sweet potato chlorotic stunt virus (SPCSV), Sweetpotato feathery mottle virus (SPFMV), Sweet potato mild mottle virus (SPMMV), Sweet potato chlorotic fleck virus (SPCFV), Sweet potato calico-like virus (SPCaLV), Sweet potato mild speckling virus (SPMSV), C-6 (a new flexious rod virus), Sweet potato latent virus (SwPLV), Sweet potato virus G (SPVG) and Cucumber mosaic virus (CMV) using Nitrocelullose Membrane ELISA (NCM-ELISA). SPCFV was the most common virus detected followed by SPCSV. SPVG was detected in seven samples representing the first report of its occurrence in Tanzania. SwPLV, C-6, CMV and SPCaLV were not detected. Whitefly population was low and aphids were rarely found in most of the fields. Orange-fleshed sweet potato cultivars grown in the surveyed areas also displayed SPVD symptoms with high incidence and severity. These results indicate that SPVD situation in Tanzania is not uniform in the major sweet potato growing areas and the significance of this virus diversity needs to be investigated.